Cultural entrepreneurship : the cultural worker's experience of entrepreneurship - Naudin, Annette (New York, NY : Routledge, 2017)
"This book explores the lived experience of cultural entrepreneurship examining the challenges associated with cultural labour including the insecurities of managing precarious working conditions. Drawing on interviews conducted with cultural workers, Cultural Entrepreneurship focuses on how individuals articulate their experience of entrepreneurship in the cultural and creative industries. Noting the importance of place, the local cultural milieu is examined as a means of situating entrepreneurial practices through cultural and enterprise policies, local networks, and significant relationships. Within this framework, the cultural entrepreneurs' stories reveal means of subverting or re-interpreting identities and the possibility for 'rethinking cultural entrepreneurship.'Aimed at researchers, academics and students investigating cultural entrepreneurship, cultural policy and cultural labour, Cultural Entrepreneurship will additionally be of value to creative industry consultants, cultural policymakers, and those setting up creative enterprises. Researchers from fields such as geography, investigating different aspects of the cultural industries in relation to cultural policy and place, will also find this book to be a useful contribution."--Provided by publisher.
Introduction -- Entrepreneurship research -- The rise of the cultural entrepreneur -- A framework for researching the cultural entrepreneur -- Identity and the cultural entrepreneur -- The significance of place -- It's who you know not what you know that matters -- Conclusion.
Keywords: Cultural industries; Entrepreneurship